The streets of Panic Park [compact disc, unabridged] - Stine, R. L. (Stine, R. L. Goosebumps HorrorLand, 2009)
The kids who are trapped in HorrorLand thought they had reason enough to panic. That was before they reached Panic Park. It seemed like the only way to escape the mysterious villain who's playing puppet-master with their lives. But Panic Park is a perilous place, and it makes HorrorLand seem like HappyLand. Now they must face their greatest fears and team up with an old foe.